# math

posted by .

How would you establish this identity:

(1+sec(beta))/(sec(beta))=(sin^2(beta))/(1-cos(beta))

on the right, sin^2 = 1-cos^2, that factor to 1-cos * `1+cos, then the denominator makes the entire right side 1+cosB
which is 1+1/sec which is 1/sec (sec+1)

qed

using sec(beta) = 1/cos(beta):

1+sec(beta))/(sec(beta))= 1 + cos(beta)

sin^2(beta)/(1-cos(beta)) =

(1-cos^2(beta))/(1-cos(beta)) =

1 + cos(beta)

This follows e.g. from:

(1 - x^2) = (1 - x)(1 + x)

and thus:

(1 - x^2)/(1 - x) = 1 + x

• math -

x=(-1)

## Similar Questions

1. ### Integration

Intergrate ¡ì sec^3(x) dx could anybody please check this answer. are the steps correct?
2. ### trig

how do you start this equation i've been tryng it for 20min. sec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x ec^6x(secxtanx)-sec^4x(secxtanx)=sec^5xtan^3x Factor out a sec^5 tan and divide thru. Left is sec^2 x = Tan^2 x Then this should …
3. ### verifying trigonometric identities

How do I do these problems? Verify the identity. a= alpha, b=beta, t= theta 1. (1 + sin a) (1 - sin a)= cos^2a 2. cos^2b - sin^2b = 2cos^2b - 1 3. sin^2a - sin^4a = cos^2a - cos^4a 4. (csc^2 t / cot t) = csc t sec t 5. (cot^2 t / csc
4. ### algebra

How do I convert the following polar expression to rectangular form?
5. ### trig

verify the identity: sec(beta)+ tan (beta)= cos(beta)/ 1-sin(beta)
6. ### Trigonometry

Prove that tan (Beta) sin (Beta) + cos (Beta) = sec (Beta) Please explain.
7. ### Trigonometry desperate help, clueless girl here

2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) …
8. ### MATH

Hi, I really need help with these questions. I did some of them halfway, but then I got stuck. Would you please help me?
9. ### calculus trigonometric substitution

∫ dx/ (x^2+9)^2 dx set x = 3tan u dx = 3 sec^2 u du I = 3 sec^2 u du / ( 9 tan^2 u + 9)^2 = 3 sec^2 u du / ( 81 ( tan^2 u + 1)^2 = sec^2 u du / ( 27 ( sec^2 u )^2 = du / ( 27 sec^2 u = 2 cos^2 u du / 54 = ( 1 + cos 2u) du / 54 …
10. ### Pre Calculus

Multiply; then use fundamental identities to simplify the expression below and determine which of the following is not equivalent. (sin x + cos x) ^2 a. 1+2sinxcosx b. sec^2x−tan^2x+2cosxsinx c.sec x + 2 sin x/sec x d. sin^2x+cos^2x …

More Similar Questions